Respuesta :

Hello!

You solve this algebraically

4w - 2(1 - w) = -38

Distribute the -2

4w - 2 + 2w = -38

Combine like terms

6w - 2 = -38

Add 2 to both sides

6w = -36

Divide both sides by 6

w = -6

The answer is -6

Hope this helps!
Astute
Let's all first, rearrange this order for us to have this problem more clear to us.

[tex] 4*w-2*(1-w)-(-38)=0 \\ \\ (4w - 2 * (1 - w)) - -38 = 0 \\ \\ Afterward,\ we \ would \ then \ want \ to \\ pull \ out \ like \ factors. \\ \\ 6w + 36 = 6 * (w + 6) \\ \\ 6 * (w + 6) = 0 \\ \\ Solve : 6 = 0 \\ \\ w+6 = 0 \\ \\ Subtract \ 6 \ from \ both \ sides: \\ \\ w = -6 \\ \\ (Your \ answer): \bf{w= -6)} [/tex]